(untitled) (Research, Society and Development, 2020)
Introduction: The present study focuses on the development of the Remote Education (ER) modality in State Public Universities in Brazil in the context of the Pandemic context. Objectives: The objective is to identify and discuss how remote education is being offered in State Public Universities in Brazil. Methodology: Descriptive study, nature of Documentary Research, with survey and analysis of the supply of RE by public Higher Education Institutions (HEIs) from all States of Brazil. As it is a research with secondary data in the public domain, ethical judgment is dispensed with. 44 websites were visited. Of these, 40 had public information about the ER and constituted the study sample. Data collection was carried out from June 17 to 25, 2020. Results and discussions: It were found that the ER started in the universities surveyed in March 47.3% and April in 21%, although 31.5% had presented a scheduled execution of activities planned to start from June to August 2020. Of the universities that offered ER, 42.1% determined the duration for the entire period of suspension of the face-to-face classes, some stipulated a deadline for execution within 10.5%, two 10.5 % or three months 5.2%; still 10.5% guided the planning monthly and 21% fortnightly or monthly. Conclusions: The COVID-19 pandemic launched a challenge to Universities: to guarantee the continuity of the teaching-learning process through non-classroom classes. However, it is clear that there was no consensus that parameters in which technology-mediated teaching should take place.